From Planning to Practice: A Comprehensive Evaluation of Thematic Lesson Plans in Madrasah Ibtidaiyah in Aceh Barat - Tengku Hafinda; Rica Alfisah; Maya Agustina (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2025)
Abstract: This study evaluated the quality of thematic instructional planning by teachers at MIN 3 Aceh Barat, focusing on its alignment with curriculum standards and thematic learning principles. Twelve classroom teachers were selected through purposive sampling. A quantitative evaluation was conducted using a checklist instrument comprising nine essential components of effective instructional design. Data were analyzed descriptively by calculating the mean percentage of criteria fulfillment. The results indicated that most instructional designs demonstrated coherent subject integration and were rated “good,” with an average achievement of 89.90 percent. However, gaps remained in formulating specific and measurable objectives, selecting pedagogical strategies aligned with learning goals, and developing authentic assessments. These findings emphasize the persistent gap between curriculum policy expectations and classroom level planning practices. By providing empirically grounded recommendations for targeted professional development, this study offers practical guidance to enhance the consistency and effectiveness of thematic instruction in primary education. Abstrak: Penelitian ini mengevaluasi kualitas perencanaan pembelajaran tematik yang dilakukan oleh guru di MIN 3 Aceh Barat, dengan fokus pada kesesuaiannya dengan standar kurikulum dan prinsip pembelajaran tematik. Dua belas guru kelas dipilih sebagai subjek melalui teknik sampling purposif. Evaluasi kuantitatif dilakukan menggunakan instrumen ceklis yang terdiri dari sembilan komponen esensial desain instruksional yang efektif. Data dianalisis secara deskriptif dengan menghitung persentase rata-rata pencapaian kriteria. Hasil menunjukkan bahwa sebagian besar desain instruksional menunjukkan integrasi mata pelajaran yang kohesif dan dinilai “baik,” dengan pencapaian rata-rata 89,90 persen. Namun, masih terdapat celah dalam merumuskan tujuan yang spesifik dan terukur, memilih strategi pedagogis yang selaras dengan tujuan pembelajaran, dan mengembangkan penilaian autentik. Temuan ini menyoroti kesenjangan yang persisten antara harapan kebijakan kurikulum dan praktik perencanaan di tingkat kelas. Dengan memberikan rekomendasi yang didukung data empiris untuk pengembangan profesional yang terarah, studi ini menawarkan panduan praktis untuk meningkatkan konsistensi dan efektivitas pembelajaran tematik di pendidikan dasar.